Nutrition Information, Element and Antioxidant Activity of Native Plant in Chiang Rai, Thailand - Chaichana, Natthiya (Science Essence Journal, 2020)
The aim of this study was to investigate nutritional content, element and antioxidant activity of Caesalpinia mimosoides Lam., Clausena excavata Burm.f. and Phlogacanthus pulcherrimus T. Anderson, the local plants consumed in Chiang Rai, Thailand. The amounts of fats, proteins, carbohydrates, crude fibers and ashes ranged from 2.27-4.25, 19.65-27.86, 41.09-54.39, 9.80-16.31 and 4.27-12.69 g per 100 g dry weight, respectively. All of plants consisted of 12 minerals (N, P, K, Ca, Mg, Mn, S, B, Na, Fe, Zn and Cu). P. pulcherrimus T.Anderson provided high content of elements especially Zn, Fe, Mg and Ca. The result of antioxidant activity analysis revealed that C. mimosoides Lam. represented the highest DPPH radical scavenging activity (92.36 umol TE/g) and also presented the highest total phenolic content (221.65 mg GE/g).